Interfacial charge transfer enhancement via formation of binary molecular assemblies on electronically corrugated boron nitride. Issue 47 (21st November 2019) - Tan, A.; Zhang, P. P.
Abstract : A weakly interacting substrate can significantly perturb the intermolecular charge transfer thus properties of donor–acceptor molecular assemblies via interfacial coupling. Abstract : Using scanning tunneling microscopy/spectroscopy (STM/STS) in conjunction with finite element simulation, we investigate the interfacial behaviors in single-component zinc phthalocyanine (ZnPc) and hexadecafluorinated zinc phthalocyanine (F16 ZnPc) molecular overlayers as well as their 1 : 1 mixed-phase superstructures on h-BN/Cu(111). We show that the formation of the binary molecular superstructure drastically increases the charge transfer between F16 ZnPc molecules and the substrate, which is attributed to the greater electrostatic stability of the binary assembly compared to that of the pure phase. This study highlights the significant complication in the design of donor–acceptor molecular thin films as the presence of the substrate, even a weakly interacting one, such as h-BN/metal, can still perturb the intermolecular charge transfer and thereby the physical behaviors of the hybrid system via interfacial processes.